2016
DOI: 10.1111/jtsb.12100
|View full text |Cite
|
Sign up to set email alerts
|

Good Friendships among Children: A Theoretical and Empirical Investigation

Abstract: Ethical dimensions of friendship have rarely been explicitly addressed as aspects of friendship quality in studies of children's peer relationships. This study identifies aspects of moral virtue significant for friendship, as a basis for empirically investigating the role of ethical qualities in children's friendship assessments and aspirations. We introduce a eudaimonic conception of friendship quality, identify aspects of moral virtue foundational to such quality, review and contest some grounds on which chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 39 publications
0
24
0
1
Order By: Relevance
“…Notably, Aristotle did not explore character friendships between children. However, speaking against the apparent consensus in the literature that friendships between children are mostly, or even exclusively, of the two lower types (in particular friendship for pleasure) are findings from one of the few empirical studies that have systematically applied Aristotle's taxonomical repertoire (Walker, Curren, & Jones, 2016; cf. also Hoyos-Valdés, 2018, who argues against the consensus).…”
Section: General Rehearsals Of Character Friendship and Some Delibementioning
confidence: 99%
“…Notably, Aristotle did not explore character friendships between children. However, speaking against the apparent consensus in the literature that friendships between children are mostly, or even exclusively, of the two lower types (in particular friendship for pleasure) are findings from one of the few empirical studies that have systematically applied Aristotle's taxonomical repertoire (Walker, Curren, & Jones, 2016; cf. also Hoyos-Valdés, 2018, who argues against the consensus).…”
Section: General Rehearsals Of Character Friendship and Some Delibementioning
confidence: 99%
“…Healy 2011, for an even-handed discussion of the literature, pro and con). For example, an empirical study of 9-10 year old children in the UK (Walker et al 2016) revealed that those children often claimed to identify and choose friends on the grounds of their moral qualities, more specifically virtues such as honesty, generosity, helpfulness and kindness. Indeed, 'the language of virtue seemed to come naturally to many of the children' (2016, p. 296; cf.…”
Section: Aristotle and Beyond: Some Basics About Character Friendshipmentioning
confidence: 99%
“…My aim here is to add at least one more element to the map of our moral and cognitive development, constituted by what happens when we engage in close relationships with non‐superiors – most especially, with friends. A recent paper in this journal addressed some of those issues empirically, by exploring the nature of friendships in late childhood, and how some of those can be conceptualized as true character friendships, conducive to the cultivation of virtue (Walker, Curren, & Jones, ). However, the present paper goes beyond this by attempting to offer a philosophically rigorous specification of the nature and developmental/educational salience of character friendships.…”
Section: Introductionmentioning
confidence: 99%